Vitamin D Gains: A look at Potatoes, Vitamin D, and Symbiotic Relationships. - Chandhoke, Gurrattan; Herman, Jennifer; Misra, Avika; Ferreira, Eric (The Meducator, 2016)
Vitamin D deficiency is a health issue that affects millions of people worldwide. In 2013, one in ten Canadians were reported to have a vitamin D deficiency. Recent research proposes that vitamin D deficiency can be addressed by creating a vitamin D-rich food source. Plant species contaminated with fungi contain traces of vitamin D, suggesting that vitamin D may be transferred from fungal organisms to plants in a mutualistic symbiotic relationship. This relationship exists between arbuscular mycorrhizae and Solanum tuberosum, a common potato plant that provides food security for millions living in Africa, Asia and South America. We propose that the pathway of radioactively labelled vitamin D from fungi to host plant can be followed in order to identify the protein responsible for transporting vitamin D. Once the genomic sequence of the transporter protein is identified, the gene can be upregulated to increase protein expression and consequently, vitamin D content in S. tuberosum crops. Understanding the specific vitamin D transfer process from fungi to plants will enable sustainable and large-scale production of vitamin D-rich food sources.